SIMULASI PENJADWALAN KEGIATAN PEMELIHARAAN MESIN PEMBANGKIT LISTRIK TENAGA DIESEL PADA PT PLN (PERSERO) SUB RAYON MANGARAN - Felix Sutisna; Chrisna Wati Makadadus (STIE Wiyatamandala, 2019)
Maintenance is the activities to maintain on machines and plant facilities. Maintenance is good to maintain the useful life of the engine. Diesel engine that is used to supply electricity power to the customer needs to be done to maintain the quality KWH produced of maintenance activities and can be used in the long term. Monte Carlo simulation techniques are used to determine scheduling of engine maintenance can reduce the likelihood of unpredictable circumstances.